Sega Selametan sebagai Upaya Menggiatkan Literasi Menulis Warga Sekolah - Eko Mulyadi (Ideguru: Jurnal Karya Ilmiah Guru, 2025)
The background of this work stems from the discovery of an anthology book published in 2021 titled "Smapta Berkarya untuk Indonesia," which features writings by teachers, employees, and outsourced staff, including security and cleaning service personnel. The urgency of this book lies in the effort to encourage and raise awareness among the school community about the culture of writing literacy, focusing on sharing their best experiences in the world of education. However, it still needs to be improved and perfected in several aspects. The purpose of this work is to invite the school community to document best practices in writing, assess participation rates among members in sharing their experiences, create an ISBN-registered anthology book, and establish the school's branding as "The Literacy School of Yogyakarta. The actions taken include issuing a circular inviting all school members—students, parents, teachers, employees, outsourced staff, and cafeteria personnel—to write about their best experiences. Additionally, literacy workshops were conducted in collaboration with academics, practitioners, and librarians from nearby high schools in Kulon Progo. The best practice essays were curated, followed by the launching of the anthology book and a book exhibition, culminating in the branding of the school as "The Literacy School of Yogyakarta." The results of this innovation indicate that after facilitating mobility orientation, school members documented their best experiences, achieving a participation rate of 57.69% among students, parents, teachers, employees, security staff, cleaning personnel, and cafeteria workers against the target. The ISBN-registered anthology book 978-623-8526-95-6, titled "Jejak Langkah: Kisah-Kisah Inspiratif Dalam Harapan dan Aksi" (Footsteps: Inspirational Stories of Hope and Action), was successfully published, and the school has been effectively branded as "The Literacy School of Yogyakarta."